2021
DOI: 10.36663/joes.v1i3.214
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Sustained Silent Reading (SSR) on Reading Comprehension in SMPN 1 Abang

Abstract: Assisting students to have good reading comprehension is essential to be accomplished during learning. Sustained Silent Reading (SSR) comes as the most used strategy to promote students’ literacy and build their reading comprehension based on the pre-observation in junior high schools in Karangasem Regency. This study aimed to investigate students’ perception of using SSR to enhance students’ reading comprehension in SMPN 1 Abang. The design of the study was mixed-method. The setting of this study is SMPN 1 Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to Bari et al (2021), consistent silent reading in descriptive texts could aid students in comprehension. Natalia et al (2021) reported that school teachers used the Silent Reading (SSR) strategy to boost students' concentration when engaging with particular texts.…”
Section: Instructing Students To Read Test Questions and Lengthy Text...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bari et al (2021), consistent silent reading in descriptive texts could aid students in comprehension. Natalia et al (2021) reported that school teachers used the Silent Reading (SSR) strategy to boost students' concentration when engaging with particular texts.…”
Section: Instructing Students To Read Test Questions and Lengthy Text...mentioning
confidence: 99%
“…instructing students to read test questions and long texts-on certain websites or PDF files (Giawa, 2022;Bari et al, 2021;Natalia et al, 2021).…”
mentioning
confidence: 99%